"From Beneath the Waves": Sea-Draugr and the Popular Conscience - Alexander Hay (John Libbey Publishing Ltd., 2018)
The sea looms large in human psychology, both as a source of guilt and a metaphor for it. One particularly evocative metaphor is in the form of the sea-draugr, a reanimated drowned corpse first mentioned in the Icelandic sagas, which in both its original form and its more modern successors, serves as a potent metaphor for recurring guilt and its consequences, as demonstrated in Icelandic sagas such as Eyrbyggja saga and Laxdæla saga. Here, mourning, guilt and lives ended before their proper resolution can be pushed aside, but they cannot be completely dismissed, as the sagas demonstrate. One other feature of the sea-draugr myth, however, is its ability to travel and manifest in other cultures. For example, while the Beowulf poem predates the sagas, there are considerable parallels between the sea-draugr and the monster Grendel, not least the latter’s aquatic nature and its mother’s grief-fuelled vengeance, in addition to nautical themes and funerary rites. The draug, or drowned seafarer, of Norwegian folklore is another good example, in form, function and, indeed, name. More recent Scottish folklore from the 19th century shows clear parallels between both sea and land-based draugr myth; for example The Wife of Usher’s Well. The supernatural fiction of WW Jacobs and MR James also have surprisingly familiar aspects to their more nautical stories, though Coleridge and Poe offer similar startling similarities. The paper will then demonstrate how the sea-draugr archetype has proceeded to become part of modern Western media narratives. Modern sea-draugr come in two varieties. The first is in the form of antagonists and monsters that are in many ways sea-draugr in all but name. For example, the vengeful leper-ghosts of John Carpenter’s The Fog or the oppressed and increasingly sentient zombies of Land of the Dead, rising from the depths of the Ohio river to take bloody revenge on the plutocrats of Fiddler’s Green. The second modern version includes those who, while not sea-draugr, or even undead per se, nonetheless ...